THE DEVELOPMENT OF HUMAN CAPITAL DISCLOSURE AND FIRM PERFORMANCE RESEARCH - Nouke Sysca Oroh (Journal of Economic, Bussines and Accounting (COSTING), 2026)
Human Capital Disclosure (HCD) has become increasingly important as organisations seek to communicate the value of employee knowledge, skills, and capabilities. However, research linking HCD and firm performance remains fragmented across accounting, strategic management, corporate governance, human resource management, and sustainability. This study maps the development and knowledge structure of the field through a systematic literature review, bibliometric performance analysis, and science mapping of 86 peer-reviewed publications published between 1982 and 2025. The findings identify four interconnected themes: intellectual capital valuation and voluntary disclosure; corporate governance and reporting quality; strategic human capital and firm performance; and sustainability and digital transformation. The literature has evolved through three phases, from foundational valuation and disclosure, through governance and integrated reporting, to sustainability-oriented and digitally enabled analysis. The Resource-Based View is the dominant theoretical lens, supported by Agency, Stakeholder, Signaling, Human Capital, and Resource Dependence theories. Recent studies increasingly apply textual analysis, machine learning, artificial intelligence, and large-scale archival methods. This study consolidates fragmented research streams and clarifies how human capital resources, disclosure practices, governance mechanisms, and stakeholder interpretations influence organisational outcomes.